New synthesis methods exploiting hypercoordination compounds of phosphorus and silicon - Andrews, Keith G (2017)
Introduction: This thesis begins with an overview of the hypercoordinate chemistry of phosphorus and silicon, chemistry in which these elements form more than their usual 3 and 4 bonds. The knowledge collected here is essential to understand the reactivity manifolds discussed in the later Chapters, and can often be surprising to chemists who rarely deviate from studies of carbon compounds. Chapter 1 epitomises this assertion, as it describes studies that resulted in a new mechanistic proposal for a previously reported phosphorus-catalysed Staudinger Ligation reaction. The proposal expounds the hidden role of in situ generated silyl ester species as enhanced reductants and acylating agents, and overturns the originally proposed phosphorus-mediated mechanism. Chapter 2 involves an in-depth study of the silyl ester species discovered in Chapter 1. First, their application in amidation chemistry is demonstrated through scope (26 examples, 33%–quant. yield) and the synthesis of API molecules (1 step synthesis of flutamide, 3-step formal synthesis of ent-lacosamide). A mechanistic study into their base-catalysed formation and reactivity in the context of amidation follows. Kinetic studies provide evidence for a rate-limiting dehydrogenation from a hypercoordinate species, first order in carboxylic acid, amine and silane. Chapter 3 develops the amidation reaction described in Chapter 2 into a direct reductive amination procedure between carboxylic acids and amines. By utilising our conditions and knowledge of the amidation procedure, we were able to incorporate an iridium-catalysed, silane-mediated reduction of the in situ generated amides to give a one-pot method to form secondary and tertiary amines (28 examples, 15-89% yield). Efforts towards exemplification to the synthesis of Maraviroc are presented. Chapter 4 also uses silyl esters productively. In this case, the silyl esters of stronger carboxylic acids, such as trifluoroacetic acid, are shown to undergo silane-mediated reduction to aldehyde-level oxidation state species, which undergo reductive amination reactions in situ. This discovery was utilised to develop a highly practical trifluoroethylation reaction of primary and secondary amines, allowing previously difficult-to-access, non- basic, highly-functionalised tertiary amine cores to be synthesised in a single step (40 compounds, 34-83% yield). Chapter 5 returns to a phosphorus theme, and provides evidence that the silyl ester species identified in Chapter 1 are also candidates to explain an enhanced phosphine oxide reduction described in a previously reported catalytic Wittig reaction. Our results are used to develop a highly active silane-mediated reduction system for the reduction of phosphine oxides. Chapter 6 focuses entirely on the hypercoordination chemistry of phosphorus. Specifically, a novel catalytic system is demonstrated to reproduce Mitsunobu chemistry. The system requires no redox additives, as it operates entirely in a P(V) manifold, producing water as the only by-product. This ‘ideal’ condensation reaction, the conversion of alcohols to esters, has been demonstrated to operate with inversion of stereochemistry at carbon, making it the first truly P-catalytic Mitsunobu reaction.